Does Technology Transfer Work? Assessing the Outcomes and Impact of the USAID-Inma Agribusiness Program - Tim Kock; James Hafer; Justen O. Smith; Jerry Turnbell (Journal of International Agricultural and Extension Education, 2014)
After years of conflict, Iraq has become unable to facilitate the development of the agricultural and business development sectors (USDA, 2010). Using the principles of technology transfer the USAID Inma Agribusiness Program (Inma) was designed to focus on agricultural development of the private sector in all 18 provinces in Iraq (USAID-Inma, 2010a; 2010b). The overall goals of Inma were to increase agricultural sales, create jobs, and assist in the adoption of new agricultural technologies. Inma invested millions of dollars in educational programs designed to strengthen the business management skills of agricultural producers and to create employment opportunities. A quantitative survey study encompassing 556 participants and a qualitative focus group study was implemented to examine the impacts of a large agricultural development effort. The study indicated participant incomes increased, farmers and business owners implemented the use of formal business plans, created stronger market linkages, new employment opportunities and sustainability. Additionally, farmers, agribusiness owners, and village elders indicated a need for additional technical and business management training programs for operating their businesses successfully.